1946
DOI: 10.3181/00379727-61-15265
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Analysis of Kala-azar Human Serum. Hypergammaglobulinemia Associated with Seronegative Reactions for Syphilis.

Abstract: 179monochloroacetic acid, and within 2 hours almost completely abolished. The effect of di-and trichloroacetic acids, while clearly defined, is much weaker and more delayed. It is important to note that here, as at all other concentrations studied, the order of decreasins effect on respiration is : monochloroacetic acid > dichloroacetic acid > trichloroacetic acid. .Acetic acid in the range of 0.01M to 0.001JI showed no effect.Within the range of 0.001pIl to 0.03M, the depression of respiration by mono-and dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1952
1952
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The role of anti-leishmanial antibody response seen in VL is unclear. Hypergammaglobulinemia has long been recognized as a detrimental factor in VL, since higher antibody levels correlate positively with disease severity and decreases after cure ( 31 33 ). It was also demonstrated that most of the circulating IgGs are not parasite-specific, as a result of polyclonal B cell activation ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of anti-leishmanial antibody response seen in VL is unclear. Hypergammaglobulinemia has long been recognized as a detrimental factor in VL, since higher antibody levels correlate positively with disease severity and decreases after cure ( 31 33 ). It was also demonstrated that most of the circulating IgGs are not parasite-specific, as a result of polyclonal B cell activation ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In visceral leishmaniasis, the level of total immunoglobulins is markedly elevated (10,11). Specific antibodies are also present.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that antibody-opsonized parasites are more efficiently taken by phagocytes that will become "permissive hosts" due to the high IL-10 and low IL-12 secretion phenotype induced by antibody Fc-receptor (FcγR) interactions [144][145][146][147]. Importantly, one of the hallmarks of human disease, is hypergammaglobulinemia (that correlates with disease severity), resultant from a polyclonal B-cell activation, being consequently most of the circulating antibodies non-parasite specific [148][149][150]. Still, and because the development and role of humoral responses in leishmaniasis is controversial and not completely understood, they may be important [151,152].…”
Section: From "Mice To Man": the Issue Of Animal Models Correlates Omentioning
confidence: 99%